(untitled) (Acta Scientiarum. Biological Sciences, 2012)
In the present study, an organophosphorus compound Coroban (active ingredient chlorpyrifos – E.C. 20%) was used. In short-term exposure the fish were subjected to 0.8 of 96h LC50 value of chlorpyrifos (1.76 mg L-1) for 96h. In long-term exposure the experiment was performed for 28 days by using 0.2 of 96h LC50 value of chlorpyrifos (0.44 mg L-1). Fish were killed on each time intervals from control and experimental (chlorpyrifos) groups after 24, 48, 72, and 96h in short-term exposure and after 7, 14, 21, and 28 days in long-term experiment. Blood samples were collected and sera were analyzed for calcium. Pituitary glands were fixed for histological studies and stained with Herlant tetrachrome and Heidenhain’s azan techniques. Short-term exposure of chlorpyrifos caused decrease in the serum calcium levels. No change was noticed in the prolactin cells of chlorpyrifos treated fish. Long-term treatment with chlorpyrifos provoked hypocalcemia. The prolactin cells of treated fish exhibited slight degranulation after 21 days whereas the nuclear volume remained unchanged. After 28 days, the prolactin cells exhibited further degranulation and the nuclear volume recorded an increase. Cytolysis and vacuolization were also visible.